Analisis Pengaruh Hubungan antara Kualitas Layanan Aplikasi BlueBox dengan Kepuasan Pengguna Menggunakan Metode Webqual 4.0 dan End User Computing Satisfaction - Irna Awalia Febriyanti; Lion Ferdinand Marini; Lorna Yertas Baisa (Universitas Islam Raden Rahmat, Malang, 2024)
BlueBox is Manokwari’s first e-commerce platform, offering a range of daily and monthly products, including groceries and snacks, with delivery services throughout Manokwari. Payment options include cash, bank transfer, and QRIS. This study aims to evaluate how the BlueBox app can improve service quality based on user satisfaction and experience, ultimately supporting UMKM success in Manokwari. The study uses the Webqual 4.0 method, covering usability, information quality, and service interaction variables, and the EUCS (End User Computing Satisfaction) method focusing on timeliness. Data analysis was conducted using the PLS-SEM approach with SmartPLS version 4.0. Survey results indicate that the average user satisfaction with the BlueBox app is 4.095, categorized as satisfied. The Timeliness variable significantly impacts user satisfaction with a P-value < 0.05, while variables such as Ease of Use, Information Quality, and Service Interaction do not show significant effects, having P-values > 0.05.